Computational interaction study of scaffold/ matrix attachment regions (S/MARS) with nuclear matrix Protein in human chromosome 3 Contactin 4(CNTN4) gene - SURESH KUMAR, (International Journal of Pharma and Bio Sciences, 2018)
The scaffold/matrix attachment regions (S/MARs) are about 300 bp to several Kb in length present in all eukaryotes. S/MARS are involved in chromatin structure as well as in transcription control. S/MARs may act as DNA elements that bind specifically to the nuclear matrix. S/MARs are generally AT-rich DNA sequences that are several hundred base pairs long and are localized in the non-coding regions of the DNA, often flanking genes. In this study, the interaction of S/MARs regions in human chromosome 3 Contactin 4 gene with nuclear matrix protein was analysed. The DNA sequences were modelled using model. it server and analysed using w3dna server. Widths of the major and minor groove of each S/MARs structure was calculated using w3dna webserver. The widths were measured as distances between phosphate groups on the two anti-parallel strands. Predictions of the binding site in S/MARs sequence were predicted using PNImodeler web server. The prediction result shows DNA length, DNA sequence, the location of binding nucleotides and number of predicted binding nucleotides from the submitted sequences. Nuclear matrix protein like cyclophilin, matrin 3, topoisomerase ii and nucleolin was considered for interaction study with S/MARs. Selected nuclear matrix protein was modelled through Raptorx server. The binding region between S/MARs and nuclear matrix protein was predicted through PNImodeler. The modelled nuclear matrix protein using RaptorX was docked with S/MARs with NPDock web server. From the molecular docking result of S/MARs and protein cyclophilin, pose prediction and second is a number of contacts occurred between S/MARs and nuclear matrix protein was analysed. Pose prediction shows the best conformation of S/MARs interaction with nuclear matrix protein. It shows the location of protein poses at S/MARs. A number of contacts show all kinds of direct interactions either polar or non-polar of favourable and unfavourable interactions. From the docking interaction study, Cyclophilin nuclear matrix protein binds with S/MARs with negative binding energy (-7.63 kcal/mol). Also based on pose prediction it has a maximum number of contacts occur between S/MARs and cyclophilin.